Towards Learning Excellence in Universities: A Critical Review of Information and Communication Technology Policies in Education in Kenya - Caroline Kiarie; Nicola-Jane Jones (University of Johannesburg, 2024)
The current reality is that technological advancement has shaped how learning is being conducted in education. Communication technology has been embraced in education by both educators and learners. However, the embracement has been slow, and this was experienced during the Coronavirus (Covid-19) pandemic, when teaching and learning had to shift and relied heavily on communication technology, but in actuality educational institutions were not ready. The virus continues to linger on and has served as a wake-up call for the education sector. This therefore makes Information and Communication Technology (ICT) an essential component in education today, not only to be implemented during crises, but also due to technological advancement and stakeholders' needs in the current times. Governments have made efforts to integrate ICT in education, as is the case in Kenya. This paper reviews the National ICT policy in Kenya since its formulation in 2006 and its revision in 2019. These two policies were national, and education was integrated into the policies. However, in 2021, an additional policy on ICT in education and training was formulated and will also be analysed in this study. The paper analyses the strategies and implementation in higher learning institutions and outlines the barriers and challenges experienced in its implementation. Accessibility and equity have been pinpointed as some of the major factors influencing ICT integration. As higher learning institutions focus on blended or hybrid learning, ICT becomes a fundamental tool to facilitate education. The paper makes recommendations based on the policy inadequacies and how to focus on ICT in education for future meaningful impact.